PENGARUH KOMPETENSI TUTOR TERHADAP HASIL BELAJAR WARGA BELAJAR KELAS XI PADA MATA PELAJARAN MATEMATIKA DI PKBM BINTANG FLOBAMORA KOTA KUPANG - Kana, Vanti Adinda; Pareira, Mariana Ikun RD; Neonufa, Samrid (Education For All, 2024)
ABSTRACT The background of the problem in this study is that tutors in class XI mathematics subjects still use conventional learning processes and methods lacking variation. The purpose of this study is to determine the influence between the competence of tutors and the learning outcomes of citizens learning equivalence package C class XI in mathematics subjects. The method in this study is quantitative with a simple linear regression test. The population in this study amounted to 72 residents learning class XI on the equivalence of package C with a sample of as much as the population because it used nonprobability sampling techniques. Hypothesis testing uses simple linear regression analysis. Based on the results of the normality test 0.018>0.05 means that the tutor's competence with the learning outcomes of learning residents is normally distributed and for the linearity test 0.759 >0.05 it means that there is a relationship between the competence of tutors and the learning outcomes of learning residents. Based on the results of a simple linear regression test, the tutor's competence had a very small influence on the results of learning students, which proved to be negative, namely -54,117. Tutor competence gets an average score of 89, meaning that the contribution of the influence of tutor competence on the learning outcomes of learning residents is 8.92% and the remaining 91.05% is influenced by other variables that were not studied in this study.